Minimally invasive surgery and neurophysiological monitoring for brainstem hemorrhage: Advancing predictive models with qEEG and TCD - Jin Wang; Huayong Wu; Bingjie Jiang (PLoS ONE, 2025)
Background Primary brainstem hemorrhage (PBSH) is a life-threatening neurological condition associated with high mortality and disability rates. Stereotactic hematoma aspiration surgery has been explored as a treatment option, and postoperative brainstem function monitoring is considered important for patient management. Objective This study aimed to evaluate the integration of minimally invasive stereotactic aspiration surgery with quantitative electroencephalography (qEEG) and transcranial Doppler (TCD) monitoring to assess brain function and improve predictive models for clinical outcomes in PBSH patients. Methods We conducted a retrospective analysis of 34 PBSH patients admitted between December 2022 and October 2023. After applying exclusion criteria, 25 eligible patients underwent stereotactic aspiration surgery within 24–48 hours of symptom onset. Both qEEG and TCD monitoring were performed preoperatively and within 24 hours postoperatively. Changes in qEEG parameters and TCD-derived hemodynamic indices were analyzed to assess surgical safety and efficacy. Results Stereotactic surgery was associated with higher rates of favorable outcomes at 90 days compared with the non-surgical group (68.75% vs. 11.11%, p = 0.01). Postoperative TCD parameters improved significantly, indicating better hemodynamic stability, though no correlation with mRS scores was found. qEEG analysis showed significant correlations between RBP δ% and mRS scores (ρ = 0.480, p = 0.015), and RBP α% (ρ = −0.456, p = 0.022). aEEG also correlated strongly with 90-day mRS scores (ρ = 0.544, p = 0.004). The combined model of hematoma volume, RBP α%, and aEEG showed the highest predictive accuracy (AUC = 0.865). Conclusion This study suggests the prognostic value of qEEG and explores the utility of combining neurophysiological monitoring with stereotactic aspiration surgery. The integration of these tools may assist in prognostic assessment for PBSH patients; however, validation in larger prospective studies is required before clinical adoption.